Volumetric reduction in large cystic jaw lesions postoperative enucleation: a longitudinal clinical study - Sarah Al-Qurmoti; Mueataz A. Mahyoub; Mohamed Elhoumed; Essam Ahmed Al-Moraissi; Zhuo‑Ying Tao; Xiaoru Hou; Jing Li; Sisi Bi; Haiyan Wu; Jing Zhang; Huanhuan Lv; Lina Jiao; et al. (BMC, 2023)
Abstract Background Enucleation, a surgical procedure, is commonly used to treat large jaw cysts, unicystic ameloblastomas and keratocysts. However, it remains unclear to what extent the jaw bone regenerates after enucleation. We aimed to evaluate the percentage and the survival analysis of jaw bone regeneration, in terms of cavity volume residual (CVR), in patients who underwent enucleation of large jaw cysts, unicystic ameloblastomas and keratocysts. Methods We collected data longitudinally from 75 patients who underwent jaw cystic lesions enucleation at the Stomatological Hospital of Xi'an Jiaotong University, between January 2015 and June 2021. All patients had both preoperative and postoperative cone-beam computed tomography (CBCT) imaging data. CBCT images were analyzed using Image J. Changes in the CVR were assessed at various follow-up time points, and the Kaplan-Meier method was utilized to evaluate the CVR over time. Results The patients had a mean age of 31.7 years (range: 5.5-72 years) with 58.66% of them being male. The postoperative CVR was 32.20% at three months, 21.10% at six months, 15.90% at 12 months, and 5.60% at 24 months. The percentage of CVR during follow-up periods for the initial size Quartile (Q)1 (212.54-1569.60 mm3) was substantially lower than those of Q2 and Q3 at and after seven months of follow-up and became statistically significant at the 12-month mark. Conclusion This study demonstrates that spontaneous bone regeneration can occur after enucleation of large jaw cysts, unicystic ameloblastomas and keratocysts, even without the use of filler materials. The initial size of the lesion had a significant impact on the outcome of cystic lesion enucleation over time. To minimize the risks associated with radiation exposure and expenses, we recommend reducing the frequency of CT imaging follow-ups for patients with small initial cavity sizes (ranging from 212.54 to 1569.60 mm3).